Cellular stress induces cap‐independent alpha‐enolase/MBP‐1 translation. Issue 16 (2nd July 2015) - Maranto, Cristina; Perconti, Giovanni; Contino, Flavia; Rubino, Patrizia; Feo, Salvatore; Giallongo, Agata
Abstract : Myc promoter‐binding protein‐1 (MBP‐1) is a shorter protein variant of the glycolytic enzyme alpha‐enolase. Although several lines of evidence indicate that MBP‐1 acts as a tumor suppressor, the cellular mechanisms and signaling pathways underlying MBP‐1 expression still remain largely elusive. To dissect these pathways, we used the SkBr3 breast cancer cell line and non‐tumorigenic HEK293T cells ectopically overexpressing alpha‐enolase/MBP‐1. Here, we demonstrate that induced cell stresses promote MBP‐1 expression through the AKT/PERK/eIF2α signaling axis. Our results contribute to shedding light on the molecular mechanisms underlying MBP‐1 expression in non‐tumorigenic and cancer cells. Abstract : MBP‐1 arises through the alternative translation of the mRNA encoding alpha‐enolase. Cellular response to stressful conditions may activate cap‐independent translation. A stress‐mediated regulatory mechanism of MPB‐1 expression is proposed. Glycolysis inhibition and ER stress induction lead to MPB‐1 expression. Inhibition or silencing of signalling actors explain the committed mechanisms.